Penerapan Poster terhadap Kepedulian Perawat dalam Mengurangi Nyeri pada Prosedur Penusukan Tumit dan Pembuluh Darah Vena pada Neonatus - Eleni Kenanga Purbasary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of posters on awareness to reduce pain in the heel and vein pricking procedure. The research design used in this study was a one-group quasi-experiment pre and post-test. The results showed an increase in nurse care by 26 people (49.1%), 95% CI in the range of 0.35-0.63 with a P-value of 0.001. In conclusion, there is an increase in nurses' care to reduce neonates' pain after the poster's application. Keywords: Nurse Care, Pain, Heel Stabbing, Poster